P21 Success rate of sputum induction in the Leicester paediatric severe asthma clinic using. (16th November 2010) - Herzallah, R; Staley, KS; Feeters, M Mc; Brightling, C; Bradding, P; Parker, D; Pandya, H; Humphreys, E; Gaillard, EA
Abstract : Background: Asthma is a common disease affecting about one in four children in the UK. It is characterised by variable airway obstruction, bronchial hyper responsiveness and influx of inflammatory cells into the bronchial mucosa. However, the mechanism of childhood asthma is still not well understood. Moreover, a subgroup of children with asthma has difficult to treat asthma, defined as persisting symptoms despite maximal conventional therapy. Management decisions in this subgroup are particularly difficult. These patients are often on high doses of steroids, with the attendant risk. A recent study in adults showed that titrating the dose of steroids to sputum eosinophils provided better asthma control without increasing the cumulative doses received by a patient. Neutrophilc airway inflammation was also shown to be a feature of some patients with difficult asthma, which may explain their poor response to corticosteroids. Therefore, knowing the inflammatory cell pattern in our cohort of children with difficult to treat asthma could potentially be a very useful tool in their management. To aid in our understanding and management of our children with difficult asthma we routinely evaluate induced sputum from children over the age of 6 years for the presence of airway inflammatory cells. A dedicated paediatric sputum lab with negative pressure facilities was made available to us by the hospital. Study Aims: To review the protocol, success rate and pattern of airway inflammation in our cohort of children with severe asthma. Methods: Review of all paediatric sputum inductions performed between March 2008 and February 2010. Results: Between March 2009 and February 2010, 57 sputum inductions were performed on 40 children, 50% males, between 6 and 18 years of age (median=12.5 years). A differential inflammation cell count was obtained from 52 of the 57 samples, giving a success rate of more than 90%. There was no significant difference in the inflammatory cell pattern between those on BTS step 3 and those on BTS steps 4 and 5. 42% of our patients had eosinophila (defined as more than 3% eosinophils), 31% had neutrophila (defined as more than 54% neutrophils), 13% had both eosinophilia and neutrophilia and only 13% had a normal inflammatory cell pattern (Abstract P21 Table 1 ). Conclusions: 1. Adequate sputum samples are obtained from most children with severe asthma when performed in a dedicated induced sputum laboratory. 2. A sputum eosinophilia was present in 55% of children studied with severe asthma. 3. The clinical value of monitoring airway inflammation in children with severe asthma using sputum induction remains to be established.